Comparison of Methods for Determining the Airflow Resistivity of Porous and Covering Materials - MELNYK, Mykhaylo; RUBACHA, Jarosław; FLACH, Artur; CHOJAK, Aleksandra; KAMISIŃSKI, Tadeusz; ZABIEROWSKI, Wojciech; IWANIEC, Marek; KERNYTSKYY, Andryi (Archives of Acoustics, 2025)
This article compares two methods for determining the airflow resistivity of porous and coating materials – a key parameter in sound absorption modelling. The analysis involves a modified static airflow measurement procedure in accordance with International Organization for Standardization [ISO] (2018), using a linear approximation algorithm (PLA), and a reverse method consisting of matching the measured absorption coefficient in an impedance tube to the Miki model. The analysis was conducted on both porous materials utilised in acoustic panel fillings and thin coverings. It is evident that both methods yield analogous outcomes for materials exhibiting low resistivity. However, for materials characterised by higher resistivity, discrepancies of up to 50 % were observed. Nevertheless, a high degree of agreement was obtained between the calculated and measured absorption coefficients. For thin coating materials, an air gap of at least 70 mm is required. For materials with a thickness of up to approximately 30 mm, differences in resistivity do not significantly affect the absorption coefficient. It is evident that both methods can be used to determine the airflow resistivity of porous materials and layered structures, supporting the effective selection of materials according to requirements.